2019
DOI: 10.2147/idr.s225383
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characterization Of Chromosome-Mediated Colistin Resistance In <em>Escherichia coli</em> Isolates From Livestock In Korea</p>

Abstract: PurposeColistin resistance in gram-negative bacteria from humans and livestock has been increasingly reported worldwide. The aim of this study was to investigate the underlying mechanisms of chromosome-mediated colistin resistance in Escherichia coli isolates from livestock in Korea.Materials and methodsThirty mcr-1-negative isolates were selected from a collection of colistin-resistant E. coli isolates collected from livestock in 2005 and 2015 in Korea. Amino acid alterations in PmrAB, PhoPQ, MgrB, and PmrD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…These modifications are associated with mutations inthe two-component systems PhoP/PhoQ and PmrA/PmrB [ 28 ]. Mutations in mgrB and pmrD genes are also known to play a role in colistin resistance in the Enterobacteriaceae , where the inactivation of MgrB, the negative regulator of the PhoPQ system, leads to overexpression of the phoPQ operon, whereas the activation of PmrD by PhoP upregulates PmrAB [ 15 ]. To address this part, the full nucleotide sequences of PhoP , PhoQ , pmrA , pmrB, mgrB and pmrD from the three colistin-resistant isolates were inspected and compared to those of E. coli K-12 MG1655 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These modifications are associated with mutations inthe two-component systems PhoP/PhoQ and PmrA/PmrB [ 28 ]. Mutations in mgrB and pmrD genes are also known to play a role in colistin resistance in the Enterobacteriaceae , where the inactivation of MgrB, the negative regulator of the PhoPQ system, leads to overexpression of the phoPQ operon, whereas the activation of PmrD by PhoP upregulates PmrAB [ 15 ]. To address this part, the full nucleotide sequences of PhoP , PhoQ , pmrA , pmrB, mgrB and pmrD from the three colistin-resistant isolates were inspected and compared to those of E. coli K-12 MG1655 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six amino acid alterations were detected in PmrB, among which E123D and Y358N mutations, located in the histidine kinase and phosphate-related domain, might affect the phosphate transfer between the two-component systems resulting in colistin-resistant isolates [ 29 ]. PmrD, which promotes the connection of PhoPQ and PmrAB two-component systems, displayed mutations at four sites (L19I, S71C, V83A and D14N), but their associations with colistin resistance have not been reported [ 15 ]. Although the double mechanism of colistin resistance, the production of mcr-1 gene along with amino acid substitution in PmrB (E123D and Y358N) or PmrA (G144S), depicted in this study in isolates EC14142 and EC13655 is considered a rare finding, it has been reported earlier by other investigators [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mgrB mutations or inactivation were suggested as major mechanisms for colistin resistance in K. pneumoniae [ 105 , 106 , 107 ], Borsa et al reported an overexpression of PhoQ and phoP genes in K. pneumoniae with wild-type mgrB gene, suggesting that other genetic regulations of the PhoPQ system may exist [ 108 ]. A very recent report from Korea described the mgrB alteration mediating colistin resistance in E. coli isolated from livestock [ 109 ]. It is noteworthy that the mutation of genes other than mgrB may contribute to enhancing PhoPQ system activity, such as ColR/ColS and CprR/CprS regulatory systems in P. aeroginosa [ 110 ], and cprR/cprS in C. jejuni [ 99 ].…”
Section: Bacterial Resistance To Polymyxins and Changes In Membranmentioning
confidence: 99%
“…The recent increase in the use of colistin in clinical practice, accompanied by its unbridled use in agriculture, have contributed to the rapid dissemination of resistance [ 14 ]. Colistin resistance is caused by decreases in the net negative charge of the outer membrane, loss of lipid A, or efflux pumps and plasmid-encoded mcr genes [ 15 ]. The mcr-1 gene uses a target site modification mechanism to protect bacteria from the action of colistin.…”
Section: Introductionmentioning
confidence: 99%